The Development of Online Educational Games with Practical Exercises Sets to Enhance Basic Mathematical Skills for Early childhood: Online Educational Games with Practical Exercises Sets, Basic Mathematical Skills, Earlychildhood. - juntarug, pakawadee; Jantahin, Thidarat; Jomhongbhibhat, Bhumbhong (Ubon Ratchathani Journal of Research and Evaluation, 2024)
The purposes of this research were 1) development of online educational games with practical exercises sets to enhance basic mathematical skills for early childhood to be effective according to the criteria 80/80 2) compare the enhance basic mathematical skills for early childhood before and after the using of online educational games with practical exercises sets 3) study student satisfaction with online educational games with practical exercises sets for early childhood. The sample used for this research was preschool students from classroom 3, semester 2, academic Year 2023, Banthon School, Affiliation Ubonratchathani Primary Educational Service Area Office 4, 19 people were obtained from cluster sampling. The research instruments included development of online educational games with practical exercises sets 12 games. Evaluation enhance basicmathematical skills for early childhood 12 item. Satisfaction questionnaire with online educational games with practical exercises sets for early childhood 5 item. The collected data were analyzed by using mean, percentage, standard deviation and t – test. The research findings were as follows: Online educational games with practical exercises sets to enhance basic mathematical skills for early childhood at level most appropriate average of 4.92, standard deviation of 0.08, so the progress of learners overall at level most appropriate. According to 94.35/89.04 which is higher than criterion the set. Enhance basic mathematical skills for early childhood after study online educational games with practical exercises sets was higher than before learning significantly at the level of .05 Early childhood is satisfied to online educational games with practical exercises sets at level most satisfied ( = 2.88, S.D. = 0.17).